Perceptive Fragility: Movement and porcelain. Issue 1 (1st June 2019) - Summerlin, Dawn
This visual essay focuses on the perception of fragility through the costume design and making process and subsequent creative interaction with performers, central to the creation of a piece of choreographed contemporary dance. Working with porcelain clay as wearable material, examples of emerging methodologies for researching costume are demonstrated. Through this practice its position as the governing element to the piece is explored as costume becomes the 'text' determining the choreography. Can the costume shape the physical and emotional responses, as its resistant, yet fragile form dictates the movement and senses of the body?